Working in palliative care: exploring community nurses' experiences of their work - Williams, Rachel (Department of Social Development, 2020)
This study explored community-based Palliative Care nurses’ experiences of their work. The aim of this study was to explore the positive aspects of working in palliative care, as well as the challenges that community-based nurses experience in their work. The coping strategies that are employed by these nurses to deal with the difficulties of their work were understood, and the participants provided recommendations to their organisations to improve their working experiences. The research was conducted in two research settings, St Luke’s Combined Hospices and Tygerberg Hospice, which are both non-profit organisations providing Palliative Care in the community. Permission was gained to conduct research by the St Luke’s Combined Hospices Research Ethics Committee, and the Palliative Care Manager at Tygerberg Hospice. A qualitative research design was used to conduct this study, and purposive sampling was used to select the sample. Fourteen nurses were interviewed using a semi-structured interview schedule, and a digital recorder was used so that interviews could be recorded accurately. Qualitative data analysis was used to arrange the data into themes, categories and subcategories. Findings from the study indicate that there is a great sense of satisfaction from working in Palliative Care and positive aspects include feelings of honour and privilege, making a difference, appreciation from patients and families, life lessons learnt, having a role in the community and working in a team. The perceived challenges were emotional challenges such as persistent rumination about work, feelings of helplessness and dealing with challenging families. Organisational challenges pertained to demanding workloads and a lack of organisational support. Personal challenges were seen as having a negative impact on the physical health and family lives of participants. Lastly, environmental challenges included issues around safety and driving to communities. Coping strategies were the support from family and friends, avoidance coping and self-care as well as group support and debriefing and support from colleagues. Lastly, recommendations include an open-door policy within the organisation, improved training and education, a better understanding of community Palliative Care, improved interaction with staff and staff reward and recognition.